Alpha-Ketoglutarate: An Effective Feed Supplement in Improving Bone Metabolism and Muscle Quality of Laying Hens: A Preliminary Study - Ewa Tomaszewska; Sylwester Świątkiewicz; Anna Arczewska-Włosek; Dorota Wojtysiak; Piotr Dobrowolski; Piotr Domaradzki; Izabela Świetlicka; Janine Donaldson; Monika Hułas-Stasiak; Siemowit Muszyński (Animals, 2020)
The aim of the experiment was to assess the effect of dietary alpha-ketoglutarate (AKG) supplementation on performance, serum hormonal indices, duodenum and jejunum histomorphometry, meat quality characteristics, bone quality traits and cartilage degradation in laying hens with a mature skeletal system. Forty-eight 30 week-old Bovans Brown laying hens were randomly assigned to a control group or the group fed the basal diet plus 1.0% AKG. The experimental trial lasted 30 weeks. The supplementation of AKG increases blood serum content of leptin, ghrelin, bone alkaline phosphatate and receptor activator of nuclear factor kappa-Β ligand, while osteoprotegerin and osteocalcin decrease. While dietary AKG was given to laying hens negatively influenced villus length, crypt depth, villus/crypt ratio and absorptive surface area in duodenum and jejunum, these changes have no effect on feed intake, weight gain, nor laying performance. In breast muscles, no significant changes in skeletal muscle fatty acid composition were observed, however, a higher shear force and decreased cholesterol content following AKG supplementation were noted, showing the improvement of muscle quality. While dietary AKG supplementation did not affect the general geometric and mechanical properties of the tibia, it increased collagen synthesis and enhanced immature collagen content. In medullary bone, an increase of bone volume fraction, trabecular thickness, fractal dimension and decrease of trabecular space were observed in AKG supplemented group. The trabeculae in bone metaphysis were also significantly thicker after AKG supplementation. AKG promoted fibrillogenesis in articular cartilage, as indicated by increased cartilage oligomeric matrix protein immunoexpression. By improving the structure and maintaining the proper bone turnover rate of highly reactive and metabolically active medullar and trabecular bones AKG showed its anti-osteoporotic action in laying hens.